Respiratory distress and Behavioural Anomalies of Indian major carp, Labeo rohita (Hamilton) Exposed to Sodium Cyanide - B. B. Hosetti, Praveen N. Dube (Recent Research in Science and Technology, 2010)
Sodium cyanide, is highly contaminating aquatic ecosystems as a toxic pollutant, was investigated in the present study for acute toxicity on freshwater fish Labeo rohita. The toxicity tests were conducted by static renewal bioassay method on the juveniles of fish was evaluated. The LC50 value of sodium cyanide to Labeo rohita was found out to be 320 µg/L. One third (106 µg/L) and one fifth (64 µg/L) of the LC50 value was selected for sublethal studies. Behavioural patterns and oxygen consumption were observed in both (1/3rd and 1/5th) sublethal concentrations (1, 5, 10 and 15 days). Sodium cyanide is highly toxic to the animal tested. Fish behaved irregular, erratic, and dartic movements, by followed hyperexcitability, loss of balance, finally settled to the bottom of the test chamber. A decrease in oxygen consumption was observed in 1/3rd (11.62% and -4.52%) and 1/5th (9.11% and -2.82%) sublethal concentrations. Fish under sublethal concentration were found to be under stress but not fatal.